Penggunaan Tawas (Al2(SO4)3) dalam Menurunkan Kadar Total Suspended Solid Air Limbah Batubara - Rahma, Cukri; Niani, Cukri Rahmi (Jurnal Optimalisasi, 2021)
Wastewater is one of the byproducts produced by coal mining companies. The wastewater contains suspended particles as well as heavy metals. Various attempts have been made to treat wastewater before it is discharged into the environment. This is done so that the waste water does not damage the environment. One way to do this is to settle suspended particles in wastewater or what is known as TSS (Total Suspended solite) using the coagulation-flocculation method. The coagulant used in this study is alum Al2 (SO4) 3. This research was conducted to determine the optimum dose or level of addition of alum into wastewater. The addition of alum is carried out in different doses, this is adjusted to the volume and discharge of waste water that is flowed to the WMP (Water Monitoring Point). The optimum dose of adding or using alum Al2 (SO4) 3 into WPM is 0.03 g / L for WMP 11, and 0.05 g/L for WMP 13.